The principles of composite construction penetrability waterproofing mortars with increased service life - Pushkarova, Kateryna; Sukhanevych, Maryna; Bondar, Kateryna (КНУБА, 2015)
Investigated waterproofing penetrability mortars inflicted on concrete structures to improve their water resistance, durability, frost resistance. Optimized binder composition.
Keywords: waterproofing mortars; portland cement; granulated blast furnace slag; natural zeolite; salts electrolytes; water absorption; durability; performance characteristics.